Acetate and propionate vs. iTBS as a novel method for cognitive dysfunction and anxiety symptoms in delayed encephalopathy after acute carbon monoxide poisoning rat - Meng, Tianyu; Zhang, Xin; Zhao, Jili; Xue, Hui; Yu, Lehua (Frontiers in Pharmacology, 2025)
BackgroundThe optimal treatment methods for delayed encephalopathy after acute carbon monoxide (CO) poisoning (DEACMP) were not identified. Thus, this study was conducted to compare the efficacies of intermittent theta burst stimulation (iTBS) and short-chain fatty acids (SCFAs) in treating cognitive dysfunction and anxiety symptoms of DEACMP rat.MethodsIn phase I, a DEACMP rat model was built to assess the inflammation levels in the hippocampus and levels of SCFAs in the serum of DEACMP rats. In phase II, DEACMP rats were randomly assigned into four groups: DEACMP + placebo, DEACMP + SCFAs, DEACMP + sham iTBS, and DEACMP + iTBS. The intervention was continued for 2 weeks. A Morris water maze and open field tests were used to assess cognitive function and anxiety symptoms, respectively.ResultsThe levels of three inflammatory factors (IL-1β, IL-6, and TNF-α) and two SCFAs (acetate and propionate) were significantly increased and decreased, respectively, in DEACMP rats. After treatment, cognitive dysfunction and anxiety symptoms were significantly improved in the DEACMP + iTBS group and the DEACMP + SCFAs (consisting of acetate and propionate) group. Both SCFAs and iTBS could significantly improve the increased levels of IL-1β, IL-6, and TNF-α in the hippocampus, and SCFAs could also improve the decreased levels of GPR41, GPR43, dopamine, and norepinephrine in the hippocampus of DEACMP rats.ConclusionThese results indicate that both iTBS and SCFA solutions consisting of acetate and propionate produced good effects on DEACMP rats by regulating inflammation levels in the hippocampus, and acetate/propionate–GPR41/GPR43–IL-1β/IL-6/TNF-α–dopamine/norepinephrine may be a potential pathway in SCFAs for the treatment of DEACMP.